Muhammad Rif`at and his reciting records - Wan Hilmi Wan Abdullah; Ahmad Asmadi Sakat; Sabri Mohamad (Universiti Kebangsaan Malaysia, 2013)
Shaykh Muhammad Rif`at is one of the famous reciters in Egypt in the era of the 90's. His stature continues evident after officially been invited as a qari to the opening ceremony of Qari al-Misriyyah Idha`at in 1934. During his involvement in the world of Quranic recitation, Shaykh Muhammad Rif`at had recited the Quran in the mosque of Fadil Basha for 25 years. His determinations to deliver and spread Holy Quran with an intermediate reading in mosques, haflah-haflah and ma’tam also have strongly influenced the next generations of qurra’. Many of the reciters like Shaykh Mustafa Isma`il, Shaykh Abu al-`Aynin Sha`isha', Shaykh `Abdul Fattah and others recognize that he has the greatness and uniqueness of its own in the art of reading the Quran. This is evidenced by some of the titles given to him as Amir al-Qurra’, Qitharah al-Sama’ and Sawt al-Malaikah by his contemporary reciters. After Shaykh Muhammad Rif`at died in 1950, then relics of his recited turath were uncovered which compiled by his friend, Zakaria Basha and compatriot Muhammad Khamis, as they managed to gather a total of 278 cds contains 19 chapters with the duration of 21 hours.